2018
DOI: 10.1016/j.schres.2017.06.015
|View full text |Cite
|
Sign up to set email alerts
|

Why transition risk to psychosis is not declining at the OASIS ultra high risk service: The hidden role of stable pretest risk enrichment

Abstract: The time course of transition risk to psychosis in UHR services is strictly associated with the time course of pretest risk enrichment. If the latter remains stable over time, as for the OASIS service, no declining transition risk is observed over the most recent years. Pretest risk enrichment is determined by recruitment and sampling strategies. This study confirms the need to control these factors in the UHR field.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
33
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 30 publications
5
33
0
1
Order By: Relevance
“… 4 ). This meta-analysis confirmed that the transition rates for psychosis had declined annually, although not in all CHR-P sites, 5 in contrast to the results of earlier studies. 6 , 7 In addition to the observation that approximately 78% of individuals at CHR-P do not go on to develop full psychosis, one-third of them only were reported to remit from the initial CHR-P status in the following years.…”
Section: Introductionsupporting
confidence: 75%
“… 4 ). This meta-analysis confirmed that the transition rates for psychosis had declined annually, although not in all CHR-P sites, 5 in contrast to the results of earlier studies. 6 , 7 In addition to the observation that approximately 78% of individuals at CHR-P do not go on to develop full psychosis, one-third of them only were reported to remit from the initial CHR-P status in the following years.…”
Section: Introductionsupporting
confidence: 75%
“…Secondly, the ultra-high-risk state is intrinsically heterogeneous 10,115 , including different subgroups 115 and varying diagnostic operationalizations 116 . Furthermore, from an epidemiological perspective, it is a spurious condition, characterized by the accumulation of a number of risk factors 117 which enrich the risk in an uncontrolled manner [118][119][120][121][122] . Ethnic minority status and urbanicity may better represent true risk factors, contributing to the development of psychotic disorders through increased socio-environmental adversities 123 .…”
Section: Discussionmentioning
confidence: 99%
“…Limiting the study is, besides a-for UHR studies-short follow-up time, the lack of MRS data at 12-month follow-up. Likewise, is the known heterogeneity of outcome of UHR individuals [54] an inherent limitation to all UHR studies.…”
Section: Discussionmentioning
confidence: 99%